Abraham's Victory over the Kings of the Four Quadrants in Light of Darius I's Bisitun Inscription. (June 2015) - Na'aman, Nadav
Abstract : The article proposes a potential ancient source that underlies the episode of Abraham's victory over the four powerful Near Eastern kings (Genesis 14). I suggest that the sought after source is Darius I's Bisitun inscription, engraved in about 520 BCE to commemorate his victories over his enemies. The author of Chapter 14 was probably acquainted with an oral version of the inscription; by imitating the image of the victorious Persian king, he depicted the heroic figure of the Israelite patriarch. The similarity between the two works can be detected in the combination of chronistic and narrative styles, the rapid movement of the plot and the shift of fronts, the abundance of names and dates, the decisive victory of the hero over his enemies and his restoration of peace in the land. Only the names of the four invading kingdoms as well as the name of Arioch might have been directly borrowed from Darius' list of peoples/lands. The composition of Chapter 14 should be dated to the time of Darius I (522-486 BCE). It might supply a terminus ante quem for the pre-Priestly Abraham's narrative in the Book of Genesis.